Micropaleontological assessment of sediments from Buor-Khaya Bay (Laptev Sea); Quaternary International; Vol. 508 - Obrezkova M. S. Mariya; Tsoy I. B. Ira; Semiletov I. P. Igor Petrovich; Vagina N. K.; Karnaukh V. N. Viktor Nikolaevich; Dudarev O. V. Oleg Viktorovich (2019, 2019)
Title screen